PENGARUH KARAKTERISTIK INDIVIDU, DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA PT. BPR HARI DEPAN - Putu Arya Budi Saputra; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The purpose of this study was to determine the effect of individual characteristics, work discipline and physical work environment on employee performance at PT. BPR Hari Depan. The population in this study were employees who worked at PT. BPR Hari Depan, namely 34 employees. Determination of the sample in this study using saturated sampling technique. The analysis technique used in this research is Multiple Linear Regression Analysis. The results of this study are Individual characteristics have a positive and significant effect on employee performance at PT. BPR Hari Depan, Work discipline has a positive and significant effect on employee performance at PT. BPR Hari Depan, Physical work environment has a positive and significant effect on employee performance at PT. BPR Hari Depan.